The correlation of MMP-9 and VEGF expressions towards nasopharyngeal angiofibroma clinical stage - Yuli Tetriana Sari; Rizalina Asnir; Ashri Yudhistira; Izry Naomi Lumbantobing (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Nasopharyngeal angiofibroma (NA) is a benign tumor with a destructive tendency, commonly affecting male adolescents. The management of NA could become quite a challenge because it is highly vascularized, and localized in an intricate area. Recently, the role of molecular biology in the development of NA is the research target for a better prognosis. Purpose: To analyze the correlation between expressions of matrix metalloproteinase (MMP-9) and vascular endothelial growth factor (VEGF) with clinical stage, and the correlation between these two markers and nasopharyngeal angiofibroma. Method: This was a descriptive analytic study using cross sectional method. Twenty-four postoperative NA cases were categorized into early and advance stages according to Chandler classification. Evaluation of MMP-9 and VEGF expressions were examined by immunohistochemistry. The correlation of VEGF and MMP-9 towards clinical stage, was analyzed using chi-square or Fisher’s exact test (α = 0.05). Result: No significant correlation between MMP-9 expression and clinical stage (p = 0.204), whereas VEGF expressions and clinical-stage showed a significant correlation (p<0.001). Statistical analysis on correlation between MMP-9 and VEGF expressions showed no significant result (p = 0.099). Discussion: MMP-9 produces pro-angiogenic and anti-angiogenic factors. MMP-9 expression does not affect the growth of NA. VEGF is a pro-angiogenic growth factor that has the most important role in tumor pathophysiology and induces vasculogenesis and angiogenesis. VEGF secretion is affected by pro-angiogenic and anti- angiogenic activities of MMP-9. Conclusion: VEGF expression is related to the clinical stage of NA. Anti-VEGF could be further investigated as an alternative treatment for NA. ABSTRAKLatar belakang: Angiofibroma nasofaring (AN) merupakan suatu tumor jinak dengan kecenderungan destruktif. Penatalaksanaan AN merupakan tantangan karena banyaknya vaskularisasi, anatomi yang kompleks dan terjadi pada usia muda. Peranan biologi molekular pada pertumbuhan AN menjadi sasaran penelitian untuk mencari prognosis yang lebih baik. Tujuan: Mengetahui hubungan ekspresi matrix metalloproteinase-9 (MMP-9) dan vascular endothelial growth factor (VEGF) dengan stadium klinis, dan hubungan kedua marker tersebut pada AN. Metode: Studi analitik deskriptif menggunakan metode potong lintang. Dua puluh empat kasus AN pasca operasi, ditentukan stadiumnya berdasarkan klasifikasi Chandler, dan dikelompokkan menjadi kategori awal dan lanjut. Evaluasi ekspresi VEGF dan MMP-9 diperiksa secara immunohistokimia. Korelasi VEGF dan MMP-9 terhadap stadium klinis dianalisis menggunakan Chi-square atau Fisher’s exact test (α =0.05). Hasil: Tidak terdapat hubungan yang bermakna antara ekspresi MMP-9 terhadap stadium klinis (p = 0,204), sebaliknya ekspresi VEGF terhadap stadium klinis menunjukkan hubungan yang bermakna (p < 0,001). Analisis statistik antara hubungan MMP-9 dan VEGF menunjukkan hasil tidak bermakna (p = 0,099). Diskusi: MMP-9 memiliki kemampuan menghasilkan faktor-faktor pro-angiogenik, dan anti-angiogenik, sehingga ekspresi MMP-9 tidak mempengaruhi pertumbuhan angiofibroma nasofaring. VEGF merupakan pro-angiogenic growth factor yang memiliki peranan paling penting dalam patofisiologi tumor dan menginduksi vaskulogenesis dan angiogenesis. Sekresi VEGF dipengaruhi oleh kemampuan pro-angiogenik dan anti-angiogenik dari MMP-9. Kesimpulan: Ekspresi VEGF berhubungan dengan stadium klinis AN. Anti-VEGF dapat diteliti lebih lanjut sebagai alternatif pengobatan pada AN.